2022
DOI: 10.3390/su141912688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Financial Inclusion on Economic Growth, Poverty, Sustainability, and Financial Efficiency: Evidence from the G20 Countries

Abstract: The main purpose of this study is to scrutinize the effect of financial inclusion on financial sustainability, financial efficiency, gross domestic product, and human development in the context of G20 nations. This study has employed annual data of 15 developed and emerging economies during the period from 2004 to 2017. The current study has utilized a single index for financial inclusion, financial sustainability, and financial efficiency by employing principal composite analysis (PCA). The outcomes of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The relationship was stronger for countries with low income and a relatively lower financial inclusion degree. These findings were also affirmed by Khan et al (2022) who suggested a positive effect of financial inclusion on economic growth, poverty, sustainability and financial efficiency for G20 countries using the generalised method of moments and the autoregression distribution lag. However these studies did not consider institutional controls in their growth models.…”
Section: Literature Review 21 Digital Financial Inclusion and Economi...mentioning
confidence: 61%
“…The relationship was stronger for countries with low income and a relatively lower financial inclusion degree. These findings were also affirmed by Khan et al (2022) who suggested a positive effect of financial inclusion on economic growth, poverty, sustainability and financial efficiency for G20 countries using the generalised method of moments and the autoregression distribution lag. However these studies did not consider institutional controls in their growth models.…”
Section: Literature Review 21 Digital Financial Inclusion and Economi...mentioning
confidence: 61%
“…Another recommendation for further research is to investigate the possible mediation effects in the link between FI and NECOT in North African economies. Possible mediators in the FI-NECOT nexus include poverty rate (Aracil et al, 2022;Khan et al, 2022), stock market development, banking sector development and sovereign credit risk (Pal & Bandyopadhyay, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by evidence across countries globally as studies based on G20 countries: "…conclusively, it means that a significant relationship subsists between financial inclusion, financial sustainability, and financial efficiency." [14] In Sub-Saharian Africa, scholars found that "there is a complimentary association (correlation) between the present degree of inclusiveness of finance and economic advancement in SSA." [3] Indian studies also identified similar results of "a positive association between economic growth and various dimensions of financial inclusion."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Like many developing countries, it endorsed and acknowledged that inclusive finance has societal implications and great potential for the joint economic development, particularly through achieving sustainable development goals (SDG). [14] As the era of digitization rise to its prime, China swiftly works to combine technology and inclusive finance to exploit benefits for the greater public, aiming to level up the state of the economy.…”
Section: Introductionmentioning
confidence: 99%